Analisis Pengaruh Penguatan Rockbolt Terhadap Kekuatan Pilar Persegi Di Tambang Bawah Tanah Dengan Pengujian Skala Laboratorium. - Jufrizal .; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. In underground mining using the room and pillar method, one way to increase the strength of the pillars is to use rockbolt reinforcement, where rockbolt reinforcement can be used if the pillar consists of compact rock, not too soft and not too hard. Because rockbolt has a significant effect on pillars, this study aims to analyze the effect of rockbolt reinforcement on square pillars by using laboratory testing of the physical and mechanical properties of pillar samples and performing numerical modeling of unreinforced and rockbolt-reinforced pillar samples. From the results of the study, it was found that the pillars without reinforcement showed an average strength value of 10.73 MPa, while the pillars with rockbolt reinforcement showed an average strength value of 12.70 MPa, so that the addition of rockbolt reinforcement showed an increase in pillar strength of 18.36%. Pillar modeling without reinforcement shows a strength factor value of 1,05, while pillar modeling with rockbolt reinforcement shows a strength factor value of 1,2, so there is an increase in the strength factor value of 14,3 %. Pillar modeling without reinforcement shows a horizontal displacement value of 5,8x x    m, while pillar modeling with rockbolt reinforcement shows a horizontal displacement value of 2,2  x   m, so there is decrease in horizontal displacement value by 37,93 %.Keywords : Pillar, Rockbolt, Physical Properties, Mechanical Properties, Modeling.